Bạo lực học đường dưới góc nhìn đạo đức học: Một nghiên cứu tổng quan - Phạm Quang Trung, Trung (Tạp chí Giáo dục, 2026)
School violence has become one of the major challenges facing contemporary education, particularly in the context of digital transformation and the increasing prevalence of cyberbullying. Although extensive research has examined school violence from psychological, educational, and sociological perspectives, studies grounded in ethical theory remain relatively limited. This paper aims to analyze school violence from an ethical perspective by clarifying the relationship between various forms of school violence and fundamental ethical values, while emphasizing the role of moral education in preventing and mitigating violent behaviors among secondary and high school students. The study employs a literature review methodology combined with analytical, synthetic, comparative, and systematic approaches to examine domestic and international research on school violence, moral responsibility, character education, and moral education. The findings indicate that school violence should not be viewed solely as an educational or social issue but also as a manifestation of moral deficiencies in cognition and behavior. Such behaviors are closely associated with violations of essential ethical principles, including human dignity, moral responsibility, justice, compassion, and empathy. Based on these findings, the paper proposes an ethical framework for analyzing school violence and highlights the importance of moral education, character education, and digital citizenship education in fostering a safe, humane, and sustainable school environment. The study also contributes to expanding the interdisciplinary discourse on school violence by integrating ethical theory into educational research and practice.